Komnas Perempuan sebagai Statute Auxialiary Bodies di dalam Penegakan Hak Asasi Manusia Perempuan di Indonesia - Laurensius Arliman S (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2017)
The poor condition of Indonesian women nationally, where the education of Indonesian women in general is still low, as well as low physical quality and inadequate non-physical, plus the social and cultural environment conditions of most Indonesian people who are less supportive of women, then the enforcement of human rights is not implemented. The May 1998 tragedy prompted the President to issue Presidential Decree No. 181 of 1998 as the legal basis for the National Commission on Violence Against Women, which was updated by Presidential Regulation No. 65 of 2005. This commission is an independent human rights commission institution established by the state to respond to the issue of women's rights as part of human rights. To realize the enforcement of women's human rights, the commission has the following tasks: a) dissemination of understanding, b) studies and research, c) monitoring, d) recommendations and regional and international cooperation.